2007
DOI: 10.1152/ajpgi.00355.2006
|View full text |Cite
|
Sign up to set email alerts
|

Persistent alterations to enteric neural signaling in the guinea pig colon following the resolution of colitis

Abstract: Functional changes induced by inflammation persist following recovery from the inflammatory response, but the mechanisms underlying these changes are not well understood. Our aim was to investigate whether the excitability and synaptic properties of submucosal neurons remained altered 8 wk post-trinitrobenzene sulfonic acid (TNBS) treatment and to determine whether these changes were accompanied by alterations in secretory function in submucosal preparations voltage clamped in Ussing chambers. Mucosal serotoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
81
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(97 citation statements)
references
References 46 publications
12
81
2
Order By: Relevance
“…Upregulation of presynaptic ATP release and/or alteration of postsynaptic P2X receptors appear to contribute in the submucous and myenteric plexes, respectively [65,106]. Recently this work has been extended to show that, following resolution of colitis, the increase in purinergic fast EPSP amplitude remains [108] and that there is an increase in fast EPSP amplitude in noninvolved tissue remote from the inflammation [109].…”
Section: Intestinal Pathologies and Purinergic Signalingmentioning
confidence: 93%
“…Upregulation of presynaptic ATP release and/or alteration of postsynaptic P2X receptors appear to contribute in the submucous and myenteric plexes, respectively [65,106]. Recently this work has been extended to show that, following resolution of colitis, the increase in purinergic fast EPSP amplitude remains [108] and that there is an increase in fast EPSP amplitude in noninvolved tissue remote from the inflammation [109].…”
Section: Intestinal Pathologies and Purinergic Signalingmentioning
confidence: 93%
“…A number of studies have demonstrated that inflammation leads to changes in the electrical and synaptic properties of colonic neurons (Linden et al, 2003a;Lomax et al, 2005), and that these changes can persist for weeks following recovery from inflammation (Krauter et al, 2007;Lomax et al, 2007). The impact of colitis-induced neuroplastic changes on propulsive motility can be investigated in the guinea pig distal colon using the GIMM system.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, inflammation-induced changes in neuronal function could be a contributing factor in IBS and refractory inflammatory bowel disease, but these changes in neuronal excitability and synaptic strength would not be detectable with current diagnostic techniques. Several inflammation-induced changes in the ENS, including AH neuron hyperexcitability, do persist beyond recovery of inflammation, 25,26 supporting the possibility that long-term changes in enteric circuitry could contribute to FGIDs.…”
Section: Neuroimmune Cross-talkmentioning
confidence: 97%